Conference On Medical And Health Sciences 2019; Invitation Poster - Pusat Pengajian Sains Perubatan, PPSP (School Of Medical Sciences, 2019)
This conference covers various medical aspects from fundamental issues to practical application of the medical and health sciences themes. Our sub-themes include: Cancer Therapeutics and Cancer Biology, AI in Medicine, Aging and Renewal Medicine, Innovation in Biosensor and Biomaterial, Mental and Community Wellness Big Data in Medicine.